A review of the Anatolian Gomphocerus Thunberg, 1815 (Orthoptera: Acrididae: Gomphocerinae) via morphological and bioacoustics characters: data suggesting a new species, a new subgenus and three new statuses - Mol, Abbas; Şi̇ri̇n Deni̇z; Taylan Mehmet Sai̇t; Sevgi̇li̇ Hasan (Zootaxa, 2023)
Gomphocerus Thunberg, 1815 (Orthoptera, Acrididae, Gomphocerinae) is an interesting genus with clavate antennae, differing from the other genera by the pyriform (pear-shaped) anterior tibiae in the male and being represented by 17 taxa species-subspecies in the Palaearctic region. Anatolian species of this genus have not been adequately studied, and almost all of them are cold tolerance species and live in high mountain meadows. The previous studies indicate that the taxa belonging to Gomphocerus have some taxonomic problems in both Turkey and the Palaearctic region. For this reason, the genus needs taxonomic revision due to its biogeographical, biodiversity, taxonomical and faunistic issues for which morphological and bioacoustics characteristics are to be used. This study was carried out between the years 2015 and 2021 at different altitudes and habitats of the mountains, where Gomphocerus specimens were collected from various localities in Anatolia. Since the species belonging to the genus have distinct morphological differences, the genus is divided into two subgenera: the nominate subgenus and a new subgenus Bolivarianus Mol, subgen. n. In addition, a new species of the nominate subgenus Gomphocerus (Gomphocerus) eyluldenizi Mol, sp.n. is described from Erzurum province (Eastern Anatolia) and when both morphology and bioacoustics characteristics are evaluated, three subspecies of the genus distributed in Anatolia are designated at species level: Gomphocerus (Gomphocerus) turcicus Mistshenko, 1951 stat. n. et sp. rev., Gomphocerus (Bolivarianus) acutus Karabağ, 1957 stat. n., and Gomphocerus (Bolivarianus) hemipterus Karabağ, 1953 stat. n. Furthermore, a key to the subgenus and species level for Anatolian members of Gomphocerus is provided with original figures, a distributional map and suggestions for conservation status according to IUCN categories are presented.